A Guerra contra o Terror nas Relações Internacionais Periféricas: o conflito entre Etiópia e Eritreia (2012) e a legitimação do discurso do uso da força contra o suporte passivo ao terrorismo - Waisberg, Tatiana (2017)
This article approaches the subject related to the use of force against terrorism in the light of international law in order to reveal the paradigm shift regarding political and legal discourse regarding this issue. The argument is developed through concrete cases that demonstrate the outcome of a new discourse regarding use of force at peripheral international relations.